En retrospektiv fallstudie av konservativ behandling av intraartikulära hovbensfrakturer, typ II och III, hos rid- och körhästar - Ohlsson, Jenny (2003)
Hospital records of 32 non-racehorses referred to ANSTI:675 and Halland Animal Hospital, Sweden, between January 1995 and September 2001 for intraarticular fractures of the third phalanx, were reviewed, and follow-up information on final outcome was collected to determine whether any injury or treatment factors could be associated with the outcome. Mean age of the horses was 8.3 years (range, 1-20 years), and follow-up time ranged from 1 to 7 years after injury. In 11 (34%) of the horses, injury involved the front limbs. Twenty-two (69%) horses returned to their original level of use. There was no statistically significant correlation between outcome and elapsed time from injury to treatment, treatment variables, or bony union in the present study. These findings support previous reports. It was concluded that horses with type II or III fractures of the distal phalanx had a fair prognosis for return to the previous level of performance.